Effect of foliar application frequency and different levels of nano fertilizer on growth and development of coriander (Coriandrum sativum L.) - Fatemeh Nejatzadeh (Heliyon, 2024)
The aim of this study was investigation of PHARMAX nano fertilizer and its frequency of foliar application effects on morphological characteristics, straw yield, fruit yield, percentage and yield of essential oil of (Coriandrum sativum L.). A factorial experiment was conducted based on a randomized complete block design with 8 treatments and 3 replications. Factors were included frequency of foliar application (tillering stage and two weeks after the first foliar application) and concentration of nano fertilizer (0, 1, 3 and 5 ml/L). Finally, the results were statistically analyzed using MSTAT-C software and the mean data were compared with Duncan test at the statistical level of 5 %. The results showed that a significant effect of number of foliar sprays on plant height, number of umbrellas/plant, number of umbrellas/square meter, number of grain/umbrella, grain yield, straw yield, single plant grain weight, single plant biomass yield, percentage and essential oil yield. In addition, different concentrations of nano fertilizer had a significant effect on most traits except the number of grain/umbrella, 1000-Grain weight and essential oil percentage. The interaction of two factors on all traits except number of umbrellas/plant, number of grain/umbrella and percentage and yield of essential oil was significant. With increasing the concentration of nano fertilizer from 0 to 5 ml/L, the number of umbrellas/square meter, grain yields, straw and essential oil yield, increased 62.5, 74.1, 74.3, 186.8 % respectively. In addition, increasing the frequency of foliar application increased the mentioned traits. According to the results, it seems that the treatment of twice-foliar application and concentration of 5 ml/L nano-fertilizer was the best treatment due to increased yield and other traits.